2008
DOI: 10.1007/s11604-007-0207-6
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoscintigraphy of pancreatic cancer in tumor-bearing athymic nude mice using 99mtechnetium-labeled anti-KL-6/MUC1 antibody

Abstract: 99mTc-labeled anti-KL-6/MUC1 antibody appears to be a promising agent as a tumor-specific radiotracer for pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Preclinical studies were investigated in BALB/ c mice bearing breast tumors indicating the accumulation of the radiocomplex at the tumor site with a high sensitivity and specificity. The results demonstrated that 111 In-DOTA-PR81 could be contemplated as a suitable probe for a prognostic imaging of antigens in oncology. 75 The results of radiolabeled anti-MUC1 PR81 mAb analogues are summarized in Table 1.…”
Section: ■ Pr81mentioning
confidence: 91%
See 4 more Smart Citations
“…Preclinical studies were investigated in BALB/ c mice bearing breast tumors indicating the accumulation of the radiocomplex at the tumor site with a high sensitivity and specificity. The results demonstrated that 111 In-DOTA-PR81 could be contemplated as a suitable probe for a prognostic imaging of antigens in oncology. 75 The results of radiolabeled anti-MUC1 PR81 mAb analogues are summarized in Table 1.…”
Section: ■ Pr81mentioning
confidence: 91%
“…54 For a radioisotope that is to be used for diagnosis, it must emit γ-rays with enough energy so that it can escape the body, and it should have a short enough half-life to be decayed away soon after the imaging is completed. For single photon-emission tomography (SPECT), γ-emitters with energies in the range from 100 to 250 keV are optimal and are mainly represented by 99m Tc, 123 I, and 111 In. High-energy positron-emitters such as 18 F, 68 Ga, 64 Cu, and 11 C can be used for positron-emission tomography (PET) by emitting 511 keV photons.…”
Section: ■ Radiopharmaceuticalsmentioning
confidence: 99%
See 3 more Smart Citations